Bees visiting the broad bean (Vicia faba L.) and the impact of border planting on their abundance and the yield improvement in Ismailia, Egypt: - M. Mohamed , Kariman; M. Ghareb, Noha; M. Kamel, Soliman; Bradshaw, Emma; Norfolk, Olivia; Shebl, Mohamed (Ecological Questions, 2023)
Incorporating flowering plants into cropping systems has the potential to actively enhance pollination and crops yields. This study evaluated whether the introduction of border planting affects bee visitation and yield of a broad bean (Vicia faba L.). Experiments were carried out in 2018 and 2019 in Ismailia, Egypt. Bee visitation and broad bean yields were compared between plots with and without border planting. Results showed that open flowers achieved higher yields than netted flowers. Apis mellifera L. was the dominant visitor, followed by four solitary bee species, Chalicodoma siculum (Rossi), Colletes lacunatus Dours, 1872, Andrena ovatula and Xylocopa pubescens (Kirby, 1802). The addition of border planting was associated with a significant increase in the abundance of all five bee visitors and the associated yields. Findings showed that flowering border plants adjacent to broad bean can actively enhance pollination services and yields of this commercially valuable crop, whilst helping to conserve vulnerable bee populations.